2021
DOI: 10.1155/2021/8774663
|View full text |Cite
|
Sign up to set email alerts
|

Functional Restoration following Global Cerebral Ischemia in Juvenile Mice following Inhibition of Transient Receptor Potential M2 (TRPM2) Ion Channels

Abstract: Hippocampal cell death and cognitive dysfunction are common following global cerebral ischemia across all ages, including children. Most research has focused on preventing neuronal death. Restoration of neuronal function after cell death is an alternative approach (neurorestoration). We previously identified transient receptor potential M2 (TRPM2) ion channels as a potential target for acute neuroprotection and delayed neurorestoration in an adult CA/CPR mouse model. Cardiac arrest/cardiopulmonary resuscitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Given the potential link between elevated GABAergic inhibition and LTP impairments in our experiments, we next asked whether TRPM2 inhibition, previously shown to restore LTP after CA/CPR (Dietz et al, 2019; Dietz et al, 2021), potentially acts through postsynaptic GABAergic changes. To test this, we measured sIPSCs from CA1 neurons and bath applied tatM2NX (2μM), a potent and specific TRPM2 inhibitor(Cruz-Torres et al, 2020), for at least 20 minutes prior to recording.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential link between elevated GABAergic inhibition and LTP impairments in our experiments, we next asked whether TRPM2 inhibition, previously shown to restore LTP after CA/CPR (Dietz et al, 2019; Dietz et al, 2021), potentially acts through postsynaptic GABAergic changes. To test this, we measured sIPSCs from CA1 neurons and bath applied tatM2NX (2μM), a potent and specific TRPM2 inhibitor(Cruz-Torres et al, 2020), for at least 20 minutes prior to recording.…”
Section: Resultsmentioning
confidence: 99%
“…Despite completion of cell death processes within days of the initial insult, we observed sustained impairments of long-term potentiation (LTP) in surviving neurons within the hippocampus, correlating with learning and memory deficits post-CA/CPR (Dietz et al, 2019; Orfila et al, 2014). More recently, we demonstrated that delayed inhibition of the Ca 2+ -permeable, transient receptor potential melastatin-2 (TRPM2) ion channel reverses impairments in hippocampal LTP and hippocampal-dependent behavioral tasks (Dietz et al, 2019; Dietz et al, 2021), implicating TRPM2 as a potential target for neurorestorative therapy following ischemia. However, the precise molecular mechanisms underlying hippocampal dysfunction and the contribution of ongoing TRPM2 activity to LTP impairment remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…172 Following juvenile GCI, inhibition of TRPM2 indicates a complex pattern of involvement in prolonged functional dysfunction (LTP and memory behavior), but not acute cell death. 99 Further, adult GCI mice signal male specific neuroprotection after acute TRPM2 channel inhibition as well as persistent TRPM2 channel activity contributing to sustained synaptic dysfunction after GCI in both males and females. 98 The differences in neuroprotection between adults and juvenile mice following GCI, including lack of acute neuroprotection in juveniles, emphasize the need for age and injury specific models.…”
Section: New Approaches To An Old Problemmentioning
confidence: 98%
“…One of the most established models of activity dependent synaptic plasticity is long-term potentiation (LTP), which is well correlated with learning and memory, as well as cognitive impairment after ischemia. 162 Studies using juvenile cerebral ischemia (both MCAO and GCI) have found impairments in long-term potentiation, 34,35,57,99 Morris water maze testing, 52,55 and contextual fear conditioning 34,35,99 days to weeks after the ischemic event. In addition, increases in thalamocortical neuron spike probability were observed 6 weeks after juvenile cardiac arrest.…”
Section: Neurorestoration As Alternative Strategy To Acute Neuroprote...mentioning
confidence: 99%
See 1 more Smart Citation